QUR’AN-BASED ECONOMIC SOCIOLOGY: FORMULATION OF A QUR’ANIC MODEL FOR THE SOCIO-ECONOMIC RESILIENCE OF MUSLIM SOCIETY IN INDONESIA - Musthofa, Musthofa; Farid, Ahmad (Universitas Nurul Jadid, 2024)
This study addresses the pressing socio-economic challenges facing contemporary Muslim societies, particularly in Indonesia, including structural poverty, income inequality, and socio-economic instability, which are exacerbated by the lack of an integrated, value-based economic framework. The primary objective of this research is to formulate a Qur’an-based model of economic sociology that offers a holistic, normative framework integrating both spiritual and material dimensions of economic life. Employing a qualitative approach through library research, the study utilizes thematic interpretation (tafsīr maudhū’ī) of selected Qur’anic verses. The analysis also engages classical Islamic scholars such as Ibn Khaldun and al-Birūnī, and contemporary thinkers including Kuntowijoyo, Jürgen Habermas, and David J. Gray, to ensure a comprehensive theoretical synthesis. The findings reveal that the Qur’anic model of economic sociology is built upon five core principles: divinity (tawhīd, ‘ibādah, hisāb) which establishes spiritual accountability in economic activity; welfare, focusing on sustenance, effort, and ecological harmony; justice, emphasizing equity, the caliphate mandate, moral accountability, and rule of law; wealth distribution, operationalized through zakat, infaq, waqf, and social safety mechanisms; and crisis anticipation to guide strategic responses in times of economic disruption. This research contributes significantly to the academic discourse by expanding the scope of Islamic economic sociology and proposing a Prophetic Sociology framework that combines humanization (amr ma’rūf), liberation (nahī munkar), and transcendence (īmān). It offers a compelling alternative to Western liberal-economic models dominated by individualism and market absolutism. The study recommends further empirical research to test the practical application of this model within various Muslim-majority contexts, and to inform policy interventions aimed at distributive justice, ethical economic governance, and sustainable social welfare systems in Indonesia and beyond.